THE EFFECT OF HOUSEWIVE INCOME CONTRIBUTION PALM OIL FARMING WORKERS IMPLEMENTATION OF FAMILY FUNCTIONS - Nissa, Hidayatun; Indrawati, Indrawati; Marnelly, T Romi (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
This research aims to uncover the impact of the contribution of income by housewives working as palm oil plantation laborers on family income and to analyze the implementation of family functions by these housewives in Bukit Kerikil Village, Bengkalis Regency. The research method employed is quantitative research using a census sampling technique. Data was collected through questionnaires, observations, and documentation. The results of the study indicate that the contribution of housewives working as palm oil plantation laborers to family income is quite significant, with the majority of respondents contributing between 41% and 50% of the family's income. Despite the insufficient income of their husbands, these housewives work as palm oil plantation laborers to help meet the family's needs. The research also evaluates the implementation of family functions by these housewives. The results show that family functions, including religious, affectionate, protective, reproductive, socialization, and economic functions, are generally well-implemented. However, some respondents believe that the implementation of affection and economic functions in their families still needs improvement. In conclusion, housewives working as palm oil plantation laborers in Bukit Kerikil Village make a significant contribution to family income and can perform family functions well. Despite facing challenges in balancing work on the plantation and household responsibilities, their efforts to achieve family welfare are commendable.